Selection and Socialization of Aggressive and Prosocial Behavior: The Moderating Role of Social‐Cognitive Processes. (19th August 2013) - Molano, Andres; Jones, Stephanie M.; Brown, Joshua L.; Aber, J. Lawrence
<x xml:space="preserve">Abstract</x> This study evaluated the extent to which fourth‐grade students (M age = 8.62) select and are influenced by their peers' aggressive and prosocial behavior and the extent to which intra‐individual social cognitions moderate these processes. Two waves of data were collected in the fall and spring of one academic year from children attending 18 New York City public elementary schools. Stochastic actor‐based social network analysis was used to evaluate whether participants modify their network or behavior in response to the behavior of their peers. Findings support an average main effect of peer influence of aggression, as well as an interaction indicating that participants with high levels of hostile attributional bias have higher odds of adopting the aggressive behavior of their peers.